Epilobium obscurum Schreb., new species in the flora of Slovenia - Strgulc-Krajšek, Simona (Natura Sloveniae, 2004)
During the revision of herbarium material (Herbarium LJU) of the genus Epilobium, a new species for the flora of Slovenia found. The specimen of Epilobium obscurum (short-fruited willowherb) had been collected in 1994 in Koroška (N Slovenia) region. Eventually, some additional localities of this species in the Pohorje Mts. and in the Štajerska (NE Slovenia) region were recorded. The present article deals with known distribution of the species in Slovenia and its most reliable distinguishing characters.
Keywords: Ecosystem; Ekosistem; flora; Plants; Rastline